2016
DOI: 10.1542/peds.2015-3199
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Suicidal Events With Atomoxetine Compared to Stimulant Treatment: A Cohort Study

Abstract: BACKGROUND: Antidepressant effects on increased suicidality in children have raised public concern in recent years. Approved in 2002 for attention-deficit/hyperactivity disorder treatment, the selective noradrenalin-reuptake-inhibitor atomoxetine was initially investigated for the treatment of depression. In post-hoc analyses of clinical trial data, atomoxetine has been associated with an increased risk of suicidal ideation in children and adolescents. We analyzed whether the observed increased risk of suicida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…We identified five studies from Europe and Asia that investigated completed suicide or suicide attempts or self-harm (59)(60)(61)(62)(63). Three studies investigated short-term effects (59,62,63) and two of them adopted within-individual designs (59,63).…”
Section: Suicidalitymentioning
confidence: 99%
“…We identified five studies from Europe and Asia that investigated completed suicide or suicide attempts or self-harm (59)(60)(61)(62)(63). Three studies investigated short-term effects (59,62,63) and two of them adopted within-individual designs (59,63).…”
Section: Suicidalitymentioning
confidence: 99%
“…A few studies using prescription databases from Europe and Asia have found null or protective effects of stimulant medications on risk of suicidal behavior (18)(19)(20)(21), but evidence from large-scale US studies is lacking. Only one comparative study between atomoxetine and stimulants is available (22), but it provided no direct estimate of the effects of these medications on risk of suicidal behavior. In addition, several clinically relevant questions are yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“… 48 Finally, a US insurance claims study of 223,303 patients between 5 and 17 years of age, who had used CS as a first-line ADHD treatment, confirmed that suicidal events (attempt or completed suicide) were rare, 26.3 per 100,000 person years during current CS use and 32.6 per 100,000 person years during former CS use. 49 …”
Section: Discussionmentioning
confidence: 99%
“…48 Finally, a US insurance claims study of 223,303 patients between 5 and 17 years of age, who had used CS as a first-line ADHD treatment, confirmed that suicidal events (attempt or completed suicide) were rare, 26.3 per 100,000 person years during current CS use and 32.6 per 100,000 person years during former CS use. 49 Adjunctive CS treatment in patients with BD In patients with BD, depressive symptoms have been associated with an increased risk of suicidal behaviour. [50][51][52] This makes patients with BD-II disorder particularly vulnerable.…”
Section: Risk Of Suicidal Behaviour With Cs In Patients With Only Adhdmentioning
confidence: 99%